Investigation of the Changes in Surface Area and FT-IR Spectra of Activated Carbons Obtained from Hazelnut Shells by Physicochemical Treatment Methods - Aziz Şencan; Mehmet Kılıç (Journal of Chemistry)
In this study, raw hazelnut shells were used to obtain charcoal by pyrolysis at 250°C. The obtained material was subjected to physical, chemical, and physicochemical treatment methods to obtain activated carbons (ACs). Effect of the treatment procedures was determined by measuring the surface area of the produced ACs. In addition, changes in the functional groups of the obtained ACs during these treatments were determined with the Fourier transform infrared spectroscopy (FT-IR). To determine the most effective chemical agent, the charcoal samples were examined for Pb(II) adsorption from aqueous solutions under different pH conditions of 4 to 6. According to the results, the most effective chemical agent was determined as Ca(OCl)2. Effect of microwave and ultrasound treatments was also examined during Pb(II) adsorption by the chemically treated AC. The results showed that chemical treatment with Ca(OCl)2, microwave treatment for 5 minutes, ultrasound treatment for 20 minutes, and pyrolysis at 700°C together were the most suitable combination enhancing the surface area of the adsorbent. This combination increased the surface area and the adsorption capacity of the adsorbent by 202 and 4.76 times, respectively, when compared to those of the raw hazelnut shell.